Application of Augmented Reality Navigation in Craniofacial Surgery for Fibrous Dysplasia - Kaiser, Will C.; Hameed, Sanaa; Muhammad, Fauziyya; Barkyoumb, David; El Amm, Christian; Smith, Zachary A. (Journal of Neurological Surgery Reports, 2025)
Fibrous dysplasia of the craniofacial bones, or craniofacial dysplasia (CFD), involves the replacement of normal bone with fibrous osseous tissue, resulting in asymmetry and distortion of the overlying soft tissue and irregular bone deposition. Treatment primarily involves surgical resection, and achieving symmetry by matching the contralateral unaffected side is crucial. However, surgical correction is challenging due to the lack of visualization of the normal contralateral structures and the need to precisely control resection depth. Although the application of an augmented reality navigation (ARN) system for CFD surgery has been documented, to our knowledge its specific use in identifying key neurovascular structures has not been reported.We present the application of an ARN system for the surgical management of an 18-year-old woman with CFD. The virtual plan was designed to visualize the extent of tumor, identify normal and abnormal vasculature, and guide the reconstruction of a normal anatomical contour.ARN was successfully integrated into the surgical workflow and optimized operative planning, identification of tumor margins, avoidance of neurovascular structures, reconstruction, and symmetric recontouring. The ability to visualize structures in real time proved to be especially beneficial for making intraoperative adjustments.ARN has significant applications for CFD surgery by providing real-time, three-dimensional simulation, and precise overlay of patient-specific anatomy and pathology, facilitating safe resection, and providing a useful reconstruction guide. To our knowledge, this report presents the first detailed description of its utility in visualizing critical neurovascular structures, offering significant potential to enhance surgical safety and patient outcomes.
Keywords: augmented reality; craniofacial; fibrous dysplasia; surgical navigation